What is Linux?—and does it work? - Goad, G. Pierre (Far Eastern Economic Review, 2000)
Part of a special section on the battle between Microsoft Windows and Linux for control of the Chinese computer operating system market. Linux is an operating system that provides the tools and rules that are used by word-processors, spreadsheets, and other software applications to create, save, retrieve, and manipulate data on a computer. The system can be modified and already has a large share of the market for servers.